PENGARUH LETHAL SERBUK DAUN OLEANDER (Nerium oleander) TERHADAP BENIH IKAN NILA (Oreochromis niloticus L.) - Abdul Karim Gaffar (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2011)
ABSTRACTInvestigation on lethal effect of leaf fowder of Nerium oleander to nile tilapia fingerlings was conducted on May 2011 in Hydrobiology laboratory of Research Instute for inland Fisheries.Static bioasays was carried out using 9 glass aquariums filled with 10 liters of test media and 10 Nile tilapia fingerlings were exposed into each aquarium.The results shows that leaf fowder of Nerium oleander were toxic to fish with 24 h, 48 h and 96h LC50 were 195.39 ppm, 51.22 ppm and 28.70 ppm respectively.Key words: Static bioasays, Nerium oleander, Oreochromis niloticus